Invitations in Spanish and Russian communicative cultures: Sociocultural context and politeness strategies - Elena Shorokhova; Palma Peña-Jiménez (Russian Journal of Linguistics, 2025)
The realization of the speech act of inviting is susceptible to situational and sociocultural context. To issue an appropriate invitation, speakers must respect cultural norms and use politeness strategies accepted in each communicative culture. The aim of this study is to identify conventionalized linguistic patterns and politeness strategies common in the realization of everyday invitations in Spanish and Russian. The analyzed corpus consists of 662 written samples collected through the Discourse Completion Task. The samples correspond to three communicative situations with different configurations of pragmatic parameters of social distance and power. The study offers a taxonomy of most productive invitation formulae in Russian and Spanish, grounded in the proposals of Blum-Kulka et al. (1989) and García (2008). The analysis is based on the politeness theory of Brown and Levinson (1987) and supported by the worksheet of the ES.POR.ATENUACION project (Albelda Marco et al. 2014). The findings indicate the presence of similar tendencies in Spanish and Russian: when greater distance and/or higher status of the interlocutor is perceived, speakers give preference to deference politeness strategies, while solidarity politeness strategies prevail in situations of closer proximity. The predominant differences are observed in the selection of invitation sub-strategies. Despite being classified as solidarity cultures, each language exhibits distinct linguistic patterns.